2017
DOI: 10.3389/fendo.2017.00274
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone (GnRH) Receptor Structure and GnRH Binding

Abstract: Gonadotropin-releasing hormone (GnRH) regulates reproduction. The human GnRH receptor lacks a cytoplasmic carboxy-terminal tail but has amino acid sequence motifs characteristic of rhodopsin-like, class A, G protein-coupled receptors (GPCRs). This review will consider how recent descriptions of X-ray crystallographic structures of GPCRs in inactive and active conformations may contribute to understanding GnRH receptor structure, mechanism of activation and ligand binding. The structures confirmed that ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 120 publications
1
61
0
1
Order By: Relevance
“…As is the case for disease‐causing mutations of other GPCRs (Tao & Conn, ), most of the ncHH‐associated GNRHR mutations that have been characterized in vitro decrease cell surface expression of the mutant GnRH‐R protein (Table ). In many cases, the mutated residues in the GnRH‐R are equivalent to residues that form conserved intramolecular (interhelical) interactions that define and stabilize the conserved GPCR structural fold (Table ) (Venkatakrishnan et al ., ; Cvicek et al ., ; Flanagan & Manilall, ), suggesting that disruption of their role in receptor folding may cause misfolding that decreases protein expression. Of the four class IV mutations of GNRHR , three involve residues that have previously been implicated in conserved GPCR activation pathways (Table ), suggesting that the mutations disrupt intramolecular interactions that mediate activation of the GnRH‐R (Flanagan & Manilall, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As is the case for disease‐causing mutations of other GPCRs (Tao & Conn, ), most of the ncHH‐associated GNRHR mutations that have been characterized in vitro decrease cell surface expression of the mutant GnRH‐R protein (Table ). In many cases, the mutated residues in the GnRH‐R are equivalent to residues that form conserved intramolecular (interhelical) interactions that define and stabilize the conserved GPCR structural fold (Table ) (Venkatakrishnan et al ., ; Cvicek et al ., ; Flanagan & Manilall, ), suggesting that disruption of their role in receptor folding may cause misfolding that decreases protein expression. Of the four class IV mutations of GNRHR , three involve residues that have previously been implicated in conserved GPCR activation pathways (Table ), suggesting that the mutations disrupt intramolecular interactions that mediate activation of the GnRH‐R (Flanagan & Manilall, ).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the mutated residues in the GnRH‐R are equivalent to residues that form conserved intramolecular (interhelical) interactions that define and stabilize the conserved GPCR structural fold (Table ) (Venkatakrishnan et al ., ; Cvicek et al ., ; Flanagan & Manilall, ), suggesting that disruption of their role in receptor folding may cause misfolding that decreases protein expression. Of the four class IV mutations of GNRHR , three involve residues that have previously been implicated in conserved GPCR activation pathways (Table ), suggesting that the mutations disrupt intramolecular interactions that mediate activation of the GnRH‐R (Flanagan & Manilall, ). The prevalence of mutations that disrupt intramolecular interactions that are conserved in GPCRs suggests that an in silico tool based on GPCR structures may better predict the effects of disease‐associated mutations in GNRHR and other GPCR genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports are available on the developing radiolabelled GnRH analogues. 125 I‐labelled GnRH was developed for receptor affinity studies in mutated GnRH receptors, permeability, protein binding, and the detection of GnRH receptors . Barda et al reported the design and synthesis of a GnRH analogue for tumor imaging as a suitable probe labeled with 99m Tc .…”
Section: Introductionmentioning
confidence: 99%
“…Aside of these GqPCR-induced effects, these central receptors were also implicated in growth arrest or apoptosis in few pathological systems [15][16][17]. For instance, cardiac hypertrophy seems to be mediated by auto/paracrine mediators acting through GqPCRs [18,19], and gonadotropin-releasing hormone (GnRH [20]) was shown to induce apoptosis of prostate cancer cells through its GqPCR [21]. Surprisingly, overexpression of constitutively active Gq induces apoptosis of COS7, CHO [22], and HeLa [23] cells as well.…”
Section: Introductionmentioning
confidence: 99%